Potential of Clove, Cinnamon and Honeysuckle in Suppressing the SARS-CoV-2 Spike Protein-ACE2 Binding, Inhibiting ACE2 Activity, and Scavenging Radicals - Huan Wu; Nora Baustian; Yanfang Li; Ethan Lee; Yinghua Luo; Margaret Slavin; Liangli (Lucy) Yu (Journal of Food Bioactives, 2024)
Water and ethanol extracts of clove (Syzygium aromaticum (L.) Merr. & L.), cinnamon (Cinnamomum verum) and honeysuckle (Lonicerae japonicae) were examined for their chemical compositions, inhibition of SARS-CoV-2 spike protein-ACE2 binding, ACE2 inhibition, and free radical scavenging activity. UHPLC-MS/MS analysis tentatively identified 34, 36, and 27 compounds in clove, honeysuckle, and cinnamon water (WE) and ethanol extracts (EE), respectively. The extracts dose-dependently suppressed SARS-CoV-2 spike protein-ACE2 binding activity and ACE2 activity. Clove and cinnamon WEs at 33.3 mg dry botanical equivalents (BE)/mL, and cinnamon and honeysuckle EEs at 3.3 mg BE/mL showed almost 100% inhibition of S-protein-ACE2 binding activity. TPC values ranged from 5.3 mg GAE/g (honeysuckle EE) to 180.0 mg GAE/g (clove EE). The highest HO·, DPPH·, ABTS·+ scavenging activity were 2181 (clove EE), 536.91 (clove WE), and 3525.1 (clove WE) µmol TE/g respectively. These data suggested the potential of these botanicals in reducing the risk of SARS-CoV-2 infection and COVID-19 severe symptom development.